2020
DOI: 10.51594/ijae.v1i1.28
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Recent Trends, Composition and Trade Intensity of Nigeria-Brazil Bilateral Relations

Abstract: This paper examines the trends, composition and trade intensity of Nigeria-Brazil bilateral trade relations for the period 2000-2017. Tables, graphs, and trade intensity index were employed. The results indicate that Nigeria's trade with Brazil has significantly recorded impressive growth. However, the share of major products exported to Brazil over the period remained insignificant with the exception of mineral fuels. The results further show that the share of major products imported from Brazil is significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…Therefore, Nigeria has no comparative advantage in all of the newly identified markets/commodities. These findings provide support for studies (Ibrahim & Iorember, 2018;Ibrahim & Sari, 2019a) that revealed a limited scope for Nigeria to increase its export to China based on only comparative advantage.…”
Section: Market Opportunities For Nigeria In the Chinese Economysupporting
confidence: 81%
See 3 more Smart Citations
“…Therefore, Nigeria has no comparative advantage in all of the newly identified markets/commodities. These findings provide support for studies (Ibrahim & Iorember, 2018;Ibrahim & Sari, 2019a) that revealed a limited scope for Nigeria to increase its export to China based on only comparative advantage.…”
Section: Market Opportunities For Nigeria In the Chinese Economysupporting
confidence: 81%
“…Therefore, Nigeria has no comparative advantage in all of the newly identified markets/commodities. These findings provide support for studies (Ibrahim & Iorember, 2018;Ibrahim & Sari, 2019a) that revealed a limited scope for Nigeria to increase its export to China based on only comparative advantage. Based on the current market condition in China, for most of the commodities which Nigeria can actually and potentially export to China, we found that there are no market opportunities in these commodities.…”
Section: Conclusion and Recommendationssupporting
confidence: 81%
See 2 more Smart Citations